Bronze Equestrian Statues from the Augustan Settlement of Waldgirmes – An Outstanding New Find of Early Imperial Statuary - Rasbach, Gabriele (Archäologischer Anzeiger, 2017)
Between 1992 and 2009 in Lahnau-Waldgirmes, Lahn-Dill-Kreis, the remains of at least two life-size bronze statues were excavated. Small finds and dendrochronological results dated the civilian Roman site to the period from 4 B.C. to around A.D. 16, that is the time of the Augustan occupation of Germania. The half-timbered forum in the centre of settlement was built on stone foundations. During research in the courtyard of the forum, five stone-robbed foundation pits for up to five statues were excavated. The largest fragment of an equestrian statue which was found – a life-size gilded bronze horse’s head – came to light in a well, the wooden fittings of which are dated by dendrochronology to the year 4 B.C.